Biomedical Anthropometric Evaluation and Conceptual Mechanical Design of Robotic System for Lower Limbs Passive-Rehabilitation on Post-Stroke Patients: Evaluación Antropométrica Biomédica y Diseño Mecánico Conceptual de un Sistema Robótico para la Rehabilitación Pasiva de Miembros Inferiores en Pacientes Post-Accidente Cerebrovascular - Martel Cervantes, Cesar (2024)
Background: Cerebrovascular accident (CVA) is one of the main causes of permanent disability, as it can cause serious brain injuries with significant physical consequences, limiting the ability to perform daily activities. Objective: This research aimed to design a robotic system of passive-continuous movement for the rehabilitation of lower limbs in adult patients with stroke, thus improving the chances of recovery of their walking mobility. Methodology: Modeling and simulation of the robotic system using Computer Aided Design (CAD), using the engineering software Autodesk Inventor Professional 2023. Results: The initial and final positions of the robotic system were obtained, as well as the simulation of passive-continuous movement. Conclusions: Taking precise measurements of a patient maximizes the possibility of implementing a functional prototype that contributes to the rehabilitation process.